2016
DOI: 10.1021/acs.analchem.6b01321
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Nondestructive, Dried Blood Spot-Based Hematocrit Prediction Method Using Noncontact Diffuse Reflectance Spectroscopy

Abstract: Dried blood spot (DBS) sampling is recognized as a valuable alternative sampling strategy both in research and in clinical routine. Although many advantages are associated with DBS sampling, its more widespread use is hampered by several issues, of which the hematocrit effect on DBS-based quantitation remains undoubtedly the most widely discussed one. Previously, we developed a method to derive the approximate hematocrit from a nonvolumetrically applied DBS based on its potassium content. Although this method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 40 publications
1
67
0
Order By: Relevance
“…This was true if 60 µL, 70 µL, or 80 µL of blood was applied. The hematocrit effect is another potential obstacle to DBS application [26]. Our results showed that hematocrits between 31% and 50% did not play a significant role as a source of variation in broad-spectrum metabolomics results ( Figure S6 and Table S12).…”
Section: Discussionmentioning
confidence: 81%
“…This was true if 60 µL, 70 µL, or 80 µL of blood was applied. The hematocrit effect is another potential obstacle to DBS application [26]. Our results showed that hematocrits between 31% and 50% did not play a significant role as a source of variation in broad-spectrum metabolomics results ( Figure S6 and Table S12).…”
Section: Discussionmentioning
confidence: 81%
“…desiccant, the differences in temperature or humidity might influence the molecular vibrations of the DBS matrix that are crucial for the NIR spectrum calculation. A time-dependent change in total hemoglobin was not assumed as others have already shown its stability in DBS[36]. A considerably slower drying or freezing of remaining moisture of the DBS matrix at reduced temperatures would be in accordance with this observation, suggesting a prolonged drying…”
mentioning
confidence: 70%
“…Third, automated processing of DBS can be made fully compatible with fully automated LC-MS/MS workstations that are about to enter clinical laboratories, allowing 'from card to report, with no manual intervention'. These systems may be equipped with tools for automated recognition of correctly deposited DBS and for coping with variables like hct, for example, via the integration of reflectance spectroscopy for hct prediction [11]. This tailoring to current (and future) workflows of routine clinical laboratories, focusing on highthroughput, is essential for more widespread implementation [12].…”
Section: Expert Opinionmentioning
confidence: 99%
“…In recent years, many efforts have been made to facilitate correct dried blood sampling, to improve DBS bioanalysis and to cope with challenges related to DBS analysis. New sampling devices are entering the market, automated analysis leads to a higher efficiency, sample throughput and reproducibility and different strategies to cope with the hct effect have been put forward [10,11]. Innovations include whole-spot analysis of volumetrically applied DBS, development of alternative dried blood sampling devices, introduction of special types of filter paper, as well as cards for generating dried plasma spots, and setup of approaches for hct prediction of DBS, allowing the correction of hct-skewed results [11,12].…”
Section: Introductionmentioning
confidence: 99%